Temporal dynamics in gastrointestinal helminth infections of sympatric mouse lemur species (Microcebus murinus and Microcebus ravelobensis) in Northwestern Madagascar - Annette Klein; Ute Radespiel; Andrea Springer; Romule Rakotondravony; Christina Strube (International Journal for Parasitology: Parasites and Wildlife)
Madagascar's lemur populations are declining in dwindling habitats due to anthropogenic expansion and changing climatic conditions. Gastrointestinal parasites can be important indicators to assess the health status of threatened species. However, parasites, hosts and the environment are connected in complex interactions. The present study aimed to disentangle the impact of seasonal and several host-specific factors (sex, species, age, reproductive status, and body mass) on endoparasitism in two small-bodied, co-occurring lemur species (Microcebus murinus and Microcebus ravelobensis) in the Ankarafantsika National Park. Helminth prevalence and egg shedding intensity was investigated via copromicroscopic examination of 810 fecal samples that were obtained from 178 individuals across an 11-month period with a longitudinal approach via repeated captures in a 30.6 ha forest area. Both mouse lemur hosts shed seven morphologically distinct egg types (assigned to Subulura baeri, unidentified Enterobiinae, Spirura sp., Lemuricola sp., two Hymenolepididae spp., one unidentified ascarid). Postmortem examination of two deceased individuals enabled assignment of adult worms to egg morphotypes of S. baeri, Spirura sp. and one Hymenolepididae sp., supported by molecular analysis. A significant seasonal variation was observed in the occurrence of the three most common helminth species S. baeri (total prevalence 71%), unidentified Enterobiinae (46%) and Spirura sp. (38%), with a higher likelihood of infection with advancing dry season. Neither host species, sex nor reproductive status had a significant effect on gastrointestinal helminth infections. Host body mass showed pronounced seasonal changes but did not differ significantly between infected and non-infected individuals. The pathogenic effects of gastrointestinal helminths therefore likely remained within compensable limits in the studied mouse lemur populations. Our findings highlight the prominent influence of seasonal changes on helminth communities. The results of combined morphologic and genetic approaches can furthermore help to overcome limitations of parasite identification via copromicroscopy by linking egg morphology to DNA sequences.